The Influence of Jigsaw-type Cooperative Learning Model on Students' Mathematics Learning Outcomes and Motivation - Amin, M; Nur, Fitriani; diah, mardhiah; Damayanti, Eka; harti, Suharti (Universitas Islam Negeri Raden Intan Lampung, 2020)
The learning process is inseparable from the learning model. The application of a learning model is an attempt to improve learning outcomes and learning motivation. This research aimed to determine the effect of the Jigsaw-type cooperative learning model on students’ motivation and learning outcomes. This research was a quasi-experimental research with a non-equivalent control group design. The research instruments used were learning motivation questionnaires and tests. Data analysis techniques used were descriptive analysis and inferential analysis using the MANOVA test. The results showed that there was an influence of the Jigsaw-type cooperative learning model on students’ motivation and learning outcomes.